Intracellular signaling mechanisms mediating catecholamine release upon activation of NPY Y1 receptors in mouse chromaffin cells - Rosmaninho-Salgado, Joana (2007)
The adrenal chromaffin cells synthesize and release catecholamine (mostly epinephrine and norepinephrine) and different peptides, such as the neuropeptide Y (NPY). NPY stimulates catecholamine release through NPY Y1 receptor in mouse chromaffin cells. The aim of our study was to determine the intracellular signaling events coupled to NPY Y1 receptor activation that lead to stimulation of catecholamine release from mouse chromaffin cells. The stimulatory effect of NPY mediated by NPY Y1 receptor activation was lost in the absence of extracellular Ca2+. On the other hand, inhibition of nitric oxide synthase and guanylyl cyclase also decreased the stimulatory effect of NPY. Moreover, catecholamine release stimulated by NPY or by the nitric oxide donor (NOC-18) was inhibited by mitogen-activated protein kinase (MAPK) and protein kinase C inhibitors. In summary, in mouse chromaffin cells, NPY evokes catecholamine release by the activation the NPY Y1 receptor, in a Ca2+-dependent manner, by activating mitogen-activated protein kinase and promoting nitric oxide production, which in turn regulates protein kinase C and guanylyl cyclase activation.